2015
DOI: 10.1093/ee/nvv117
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Variation of two Pacific CoastDrosophila suzukii(Diptera: Drosophilidae) Populations

Abstract: The vinegar fly, Drosophila suzukii (Diptera: Drosophilidae), is a recent invader in North America that has become a serious threat to small fruit production. It was first detected in California in 2008 and in Washington state in 2009. In this study, D. suzukii populations from the area of the original detection on California's central coast and from eastern Washington, the United States, were sampled over a 3-year period to determine genetic variation in both using microsatellite markers. Six different loci w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The high level of heterozygosity could be explained by good adaptation to new ranges due to a favourable environment, their reproductive power, and the absence or limited presence of natural competitors and predators [ 57 , 58 ]. Bahder et al found that populations from Washington were much less polymorphic than those in California, suggesting a recent strong population bottleneck associated to the recent invasion of the former [ 22 ]. Washington has a much cooler climate than California, similar to the contrast between Trentino and the rest of Italy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high level of heterozygosity could be explained by good adaptation to new ranges due to a favourable environment, their reproductive power, and the absence or limited presence of natural competitors and predators [ 57 , 58 ]. Bahder et al found that populations from Washington were much less polymorphic than those in California, suggesting a recent strong population bottleneck associated to the recent invasion of the former [ 22 ]. Washington has a much cooler climate than California, similar to the contrast between Trentino and the rest of Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Jeffrey and colleagues based their research on the use of six X-linked genes and suggested that the invasions of the USA and Europe are two independent events [ 21 ]. Bahder et al in particular analysed samples of D. suzukii populations collected in California and Washington and determined that while D. suzukii in the former region had high levels of genetic variation, the latter was highly monomorphic [ 22 ]. Furthermore, Fraimout’s group investigated Hawaiian and Spanish populations by exploiting microsatellite markers, finding a significant level of genetic differentiation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two aspects could be inferred from the absence of resistance after selection with malathion over 30 generations in SWD: (1) the initial cherry and blueberry collected populations had low genetic variability or (2) the microbial degradation of malathion was facilitated by yeast and bacterial complexes originating from the adults. In the first case, a genetic bottleneck in Pacific northwest populations of SWD has previously been documented and could contribute to the lack of change in malathion susceptibility in recently established BC SWD populations. A selection with contact insecticides under field conditions could induce monogenic resistance by fixing onto the dominant allele through mutations should the SWD genetic reservoirs exist .…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the course of the invasion of D. suzukii , its genetic diversity changed through bottlenecks and admixture events (Fraimout et al., ). A comparison of the host genotype across neutral markers (6–28 microsatellites) and six X‐linked loci in coding and noncoding sequences indicated relatively high intraspecific genetic variation within and between populations in the invaded regions (Adrion et al., ; Bahder, Bahder, Hamby, Walsh, & Zalom, ; Fraimout et al., , ). It is therefore reasonable to assume that there is substantial intraspecific genotypic variation in the invaded populations that can contribute to the variable D. suzukii –parasitoid outcome.…”
Section: Step 3: Understanding Variation In D Suzukii–parasitoid Intmentioning
confidence: 99%